SISTEM INFORMASI AKUNTANSI DAN GAYA KEPEMIMPINAN PENGARUHNYA TERHADAP KINERJA INDIVIDU - Nugrahini Kusumawati; Via Ultuvlia (Gapenas Publisher, 2022)
The purpose of this study is to determine the influence of accounting information systems and leadership styles on individual performance, both partially and simultaneously. The method used in this study is quantitative with a correlation approach. The data collection technique was carried out by the survey method using the Likert scale. The population is 113 employees of trading companies. The sample determination technique uses the purposive sampling technique, namely employees who are directly related to the Accounting Information System as many as 108 respondents while 5 people are not included as respondents because they are not directly related to the accounting information system, namely the delivery of goods. The results of this study show that there is an influence of accounting information systems, leadership styles on individual performance both partially and simultaneously